Socio Economic Reintegration on the Fit of Migrant Worker Returnees Policy and Process and Life Satisfaction of Ugandan Migrant Worker Returnees from Middle East - SSejinja, David; Rukanyangira, Nazarious; Kiyingi, Pio Frank (American Journal of Public Policy and Administration, 2023)
Purpose: The current study was undertaken to establish the contribution of socioeconomic reintegration on the fit of migrant worker returnees policy and process and life satisfaction of Ugandan migrant worker returnees from middle east so as to come up with a unified model for improvements in Uganda. Its objectives main objective was to explore the mediating effect of socio economic reintegration on the fit of migrant worker returnees' policy and process and life satisfaction of Ugandan migrant worker returnees from Middle East. Materials and Methods: In an effort to address the set objectives, a cross-sectional survey design which followed both quantitative and qualitative research approaches was adopted. Data was collected from a total quantitative sample of 218 Ugandan migrant worker returnees from Middle East. A qualitative sample of 25 managers of registered labour export companies and ministry officials in Uganda was determined by saturation point approach. The data was analysed at descriptive and inferential level, and later a Path Equation Model was fitted through Structural Equation Modelling in Stata Version 14.0. Findings: The results indicated exists a positive relationship on the use of Social Reintegration and life satisfaction of the Uganda migrant returnees (r = 0.397 statistically significant since the associated p - value of 0.000 is less than 0.05 (p< 0.001). Results also showed shows that there exists a positive relationship between returnee policy implementation and social economic reintegration of the Uganda migrant returnees (r = 0.398). This relationship is statistically significant since the associated p - value of 0.000 is less than 0.05 (p < 0.001). The study concluded that that sufficient evidence substantiates significant relationship exists between socio economic reintegration and life satisfaction. Implications to Theory, Practice and Policy: Finally, the socio economic reintegration and the other strategies had a total causal effect of 92.8% on life satisfaction. However, the life satisfaction referred to only applied to the current environment which did not promise continued Survival into the future. Given that fact the study has proposed the Sustainable Penchant Socioeconomic Partaking Model (SUPSEP MODEL) which guarantees not only life satisfaction but also sustainability. This, therefore, means that if the new Model is adopted, the migrant worker returnees' will not only be provided a good life satisfaction for a short period of time but will get it for many years to come. The SUPSEP Model is, henceforth, the current study contribution to knowledge.